MANFAAT HASIL BELAJAR FASHION PRODUCT SEBAGAI KESIAPAN MERINTIS USAHA BRIDAL ACCESSORIES - Niesma Restimah; Marlina Marlina (Fesyen Perspektif, 2016)
Bridal accessories is one business opportunity that is quite promising considering not too many businesses that are opened specifically sells bridal accessories readiness to open a possible Bridal Accessories arise after getting the knowledge and skills of one of the subjects Fashion Product. The aim of this study was to obtain data on The Benefit Of Studying Results Fashion Product As Pioneering Readiness Of The Business Bridal Accessories . The method used in this research is descriptive method with data collection tool in the form of a questionnaire. The population in this study is a student concentration Fashion Design Maranatha Christian University class of 2012, which amounted to 30 people. The results showed that more than half of the students know The Benefit Of Studying Results Fashion Product As Pioneering Readiness Of The Business Bridal Accessories effort in terms of basic competence basic concepts of accessories, manufacture of accessories design, material and manufacturing accessories manufacture accessories. The conclusion from this study showed that more than half of student concentration Fashion Design Maranatha Christian University class of 2012 has felt The Benefit Of Studying Results Fashion Product As Pioneering Readiness Of The Business Bridal Accessories . Results of this study are expected to be used as input in developing learning materials.